2016
DOI: 10.3390/ma9060493
|View full text |Cite
|
Sign up to set email alerts
|

Creep of Polycrystalline Magnesium Aluminate Spinel Studied by an SPS Apparatus

Abstract: A spark plasma sintering (SPS) apparatus was used for the first time as an analytical testing tool for studying creep in ceramics at elevated temperatures. Compression creep experiments on a fine-grained (250 nm) polycrystalline magnesium aluminate spinel were successfully performed in the 1100–1200 °C temperature range, under an applied stress of 120–200 MPa. It was found that the stress exponent and activation energy depended on temperature and applied stress, respectively. The deformed samples were characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Therefore, it was suggested that the SPS apparatus could be used as an accurate creep testing tool [12]. Such capabilities have already been demonstrated for both ceramics [12,13] and metals [14,15]. It is worthy to note that SPS creep test results have already shown good agreement with previously reported data obtained by conventional testing methods for the same materials at similar temperature/pressure ranges [12][13][14][15].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Therefore, it was suggested that the SPS apparatus could be used as an accurate creep testing tool [12]. Such capabilities have already been demonstrated for both ceramics [12,13] and metals [14,15]. It is worthy to note that SPS creep test results have already shown good agreement with previously reported data obtained by conventional testing methods for the same materials at similar temperature/pressure ranges [12][13][14][15].…”
Section: Introductionmentioning
confidence: 63%
“…Such capabilities have already been demonstrated for both ceramics [12,13] and metals [14,15]. It is worthy to note that SPS creep test results have already shown good agreement with previously reported data obtained by conventional testing methods for the same materials at similar temperature/pressure ranges [12][13][14][15]. Moreover, it has been proposed that the SPS apparatus' ability to apply an electric current to the sample makes it possible to investigate to some extent electro-plastic effects in conductive materials during high temperature deformation Spark plasma sintering (SPS) is an advanced pressure-assisted sintering technique, which utilizes an electric current for heat generation within conductive tooling and powder compacts [9,10].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The modernized SPS device allowed for gaining information about process dynamics, which was key information during the optimization of the SHS parameters. Most SPS devices track only three basic parameters: maximum temperature, time and applied pressure [ 2 , 30 ]. An increased number of tracked parameters allowed for continued and detailed process monitoring, which was crucial for understanding the phenomena and stages of the sintering.…”
Section: Discussionmentioning
confidence: 99%
“…Each model requires the identification of creep parameters that will be developed later in this study. In most works, those parameters are identified experimentally, which requires a specific equipment and multiple experiments [15][16][17][18]. The objective of this study is to develop a new approach that will allow to identify numerically the creep parameters based on only one experimental trial per material.…”
Section: Introductionmentioning
confidence: 99%